Indigenous ethnobotanical remedies practiced to cure feminine diseases in tribal communities of kashmir himalayas - Hamayun Shaheen; Muhammad Ejaz Ul Islam Dar; Zahid Ullah (International Journal of Phytomedicine, 2014)
Women’s reproductive cycles are very clinical and complex, having unwanted medical conditions. Himalayan Women have been trying to enhance their fertility and regulate their reproductive cycles throughout the history by practicing ethnomedicinal remedies, as they are reluctant to expose their feminine problems to doctors due to psychological, social and religious barriers. Present study reveals the ethnomedicinal recipes practiced by mountain women in Kashmir Himalayas for feminine diseases. Data was acquired by planned biological inventories, exclusive interviews and direct observations in the field. A total of 36 plants belonging to 27 families were recorded being practiced for feminine diseases in 43 different recipes. Major feminine diseases treated by ethnomedicine were menstrual disorders (32%); birth pain and bleeding (16%); Contraception and abortion (16%); enhancing fertility (9%), Sexual potency (9%) and Lactation (7%). Major plant parts utilized in recipes were roots (32%), whole plant (16%), leaves (16%), Seeds (9%), latex (7%) and fruit (7%). Decoctions (41%), raw plant parts (24%) and extracts (13%) were prevalent modes of ethnomedicinal remedies. 79.6% respondents were effectively involved in ethnomedicinal practices to treat feminine diseases. An increasing trend towards modern medical treatment was observed in younger generation correlated with higher education level. Paper discuses the ethnomedicinal treatment of feminine diseases in qualitative as well as quantitative methodology and elaborates how the local folklore can be used at regional levels to add new cures in feminine pharmacopeia.